Hating the Enemy?: Ethics in 2 John - Frey-Shoukry, Zacharias (Studien zum Neuen Testament und seiner Umwelt. Serie A, Aufsätze, 2024)
The second Epistle of John advises that one should neither greet nor receive into their own houses those who “do not confess that Jesus Christ has come in the flesh” (v. 7): “Do not receive into the house or welcome anyone who comes to you and does not bring this teaching” (v. 10). The purpose of this article is to answer the question of whether these verses encourage believers to hate their enemy. To accomplish this goal, I first analyze the ethics of 2 John as a whole. This analysis is necessary to understand the ethical context of the problem at hand. Second, I compare the ethical views of 2 John with other early Christian conceptions, especially the love of enemies (“Feindesliebe”) and hospitality. Third, in light of these contexts (the epistle itself and other early Christian literature), I consider whether 2 John advocates the highly problematic hatred of one’s enemies (“Feindeshass”) and will outline central ethical insights that are relevant to contemporary issues. It will be shown, for example, that Christian intolerance can be traced back to texts like 2 John. Therefore, it is important to develop critical readings of biblical texts, especially when they encourage hostile behavior.